Optimalisasi Media Game Edukasi Fisika (GEMIKA) Berbasis Wordwall dalam Meningkatkan Literasi Digital Kelas X SMANKOR Maluku Utara - Tamarengki, Olfiane; Lana, Kartini (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
This study aims to describe the increase in digital literacy of class X students at SMANKOR North Maluku after using the Wordwall-based Physics Education Game Media (GEMIKA). The background of this study is based on the low level of digital literacy of students and the limited use of technology-based learning media in schools. The method used is descriptive research with a qualitative approach. The subjects in this study were 31 class X students selected through purposive sampling techniques. The instruments used in data collection included participatory observation, interviews, and questionnaires to measure the level of digital literacy before and after using GEMIKA. Data analysis was carried out through the Miles, Huberman, and Saldana (2019) model which includes data reduction, data presentation, and drawing conclusions.The results showed that there was a significant increase in all aspects of digital literacy after the implementation of Wordwall-Based GEMIKA media. The average percentage of digital literacy increased from 58.2% to 73.6%. In detail, the aspect of media usage increased from 40.5% to 76.2%, digital literacy from 55.6% to 70.5%, learning motivation from 60.7% to 75.0%, and digital technology skills from 57.8% to 72.6%. In conclusion, the use of GEMIKA media based on Wordwall has proven effective in improving students' digital literacy, motivation, and technology skills. This study also shows that the integration of digital-based educational games can be an innovative solution in science learning, especially physics, in areas with limited technological infrastructure.